1989
DOI: 10.1128/jb.171.9.4679-4685.1989
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational regulatory system for nitrogenase activity in Azospirillum spp

Abstract: The mechanism for "NH4+ switch-off/on" of nitrogenase activity in Azospirillum brasilense and A. lipoferum was investigated. A [39]) has been well studied in the purple nonsulfur photosynthetic bacterium Rhodospirillum rubrum. In R. rubrum, the loss of cellular nitrogenase activity during switch-off by NH4Cl is correlated with the covalent modification and resulting inactivation of dinitrogenase reductase (13). The covalent modification consists of the ADP-ribosylation of dinitrogenase reductase at . This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 37 publications
(35 reference statements)
2
46
0
Order By: Relevance
“…For the photosynthetic purple nonsulfur bacterium Rhodospirillum rubrum and other members of the Alphaproteobacteria, like Azospirillum brasilense, Azospirillum lipoferum, and Rhodobacter capsulatus, it has been shown that nitrogenase activity is rapidly switched off as a consequence of either the addition of ammonium or energy depletion (10,26,32,35,54). One subunit of the nitrogenase Fe protein is modified under switch-off conditions, with the modification leading to the inactivation of the enzyme.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the photosynthetic purple nonsulfur bacterium Rhodospirillum rubrum and other members of the Alphaproteobacteria, like Azospirillum brasilense, Azospirillum lipoferum, and Rhodobacter capsulatus, it has been shown that nitrogenase activity is rapidly switched off as a consequence of either the addition of ammonium or energy depletion (10,26,32,35,54). One subunit of the nitrogenase Fe protein is modified under switch-off conditions, with the modification leading to the inactivation of the enzyme.…”
mentioning
confidence: 99%
“…In A. brasilense, A. lipoferum, and R. capsulatus, draT and draG orthologs were discovered as well (10,35). Moreover, in various genome projects (http://www.ncbi.nlm.nih.gov/genomes /lproks.cgi/), draG-like sequences and few draT orthologs can be identified.…”
mentioning
confidence: 99%
“…However, this regulation has been well characterized only in Rhodospirillum rubrum, Azospirillum brasilense, Azospirillum lipoferum, and Rhodobacter capsulatus, in which it involves reversible mono-ADP ribosylation of dinitrogenase reductase, catalyzed by the dinitrogenase reductase ADP-ribosyl transferase (DRAT)/dinitrogenase reductase activating glycohydrolase (DRAG) regulatory system (5,6,17,30). DRAT (the gene product of draT) catalyzes the transfer of the ADP-ribose from NAD to the Arg-101 residue of one subunit of the dinitrogenase reductase dimer and thereby inactivates the enzyme.…”
mentioning
confidence: 99%
“…The DRAT-DRAG system has been characterized in other nitrogen-fixing bacteria, such as A. brasilense (9,42) and Rhodobacter capsulatus (24), and it negatively regulates nitrogenase activity in response to exogenous NH 4 ϩ or to energy limitation in the form of darkness (in the cases of R. rubrum and R. capsulatus) or anaerobiosis (in A. brasilense). Both DRAT and DRAG activities are themselves subject to posttranslational regulation under these conditions (10,14,19,39,42), but neither the mechanisms of their regulation nor the signal transduction system that controls it is understood.…”
mentioning
confidence: 99%